Plic plac ploc, valeurs rythmiques d’un iconotexte en réception en classe maternelle - Marie-Claude Javerzat (Strenae)
Our study concerns the reception of an iconotextual picture book whose potential rhythmic values are numerous and diversified, in the text, the image, and in the course of its reading. The analysis of two situations of reading the picture book to a kindergarten class of children aged 4 to 5 years old, reveals the teacher’s and the pupils’ capacities to co-develop its meaning as defined by Meschonnic, starting with the work’s possibilities.